Breaking Academic Silos: Pedagogical Recommendations for Equitable Obesity Prevention Training and Research During an Age of Nutrition Polarization - Salima F. Taylor, MS; Danielle M. Krobath, PhD; Adolfo G. Cuevas, PhD; Erin Hennessy, PhD; Susan B. Roberts, PhD (Elsevier, 2024)
Introduction: Obesity is a preventable chronic condition and a risk factor for poor health and early mortality. Weight stigma and weight-neutral medicine are popular topics in social media that are often at odds with current medical guidelines on obesity treatment and prevention. This conflict may erode the public's trust in science, impede research progress on preventing obesity in marginalized groups, and uphold the ongoing and historical lack of diversity among nutrition trainees. Methods: The authors conducted a series of student-led dialogue sessions with nutrition graduate students in Boston, Massachusetts, from March to May 2023 to understand perceptions of obesity research, health equity, and racism and discrimination. This article summarizes the lessons learned and provides pedagogical recommendations for jointly addressing obesity at the population level and the recruitment, training, and retention of diverse scholars, clinicians, and public health practitioners. Results: Dialogue sessions revealed that students perceive a disproportionate focus on the harms of obesity as a chronic disease, highlighting that inadequate attention is given to weight stigma and discrimination. Some participants believed that weight-based discrimination is equally detrimental to individual health and wellbeing as having obesity. Discussions also emphasized the need to pinpoint the multidimensional and cultural manifestations of weight stigma, which necessitates collaboration across social sectors and academic disciplines. Students recognized the urgent need to apply an equity lens to obesity research and teaching but felt limited in their access to experts within nutrition science who specialize in racism, discrimination, eating disorders, and weight stigma. Conclusions: This study identified concrete opportunities for urgently needed new training and research in population-level obesity prevention, emphasizing antiracism, harm reduction, and elimination of stigma and bias across multiple levels of science and society. Overall, the decision to use the BMI within pedagogy and training must be explicitly stated-research, population surveillance, decision-making, or treatment pedagogy and training-while acknowledging its strengths and limitations across diverse settings. Finally, the social determinants of obesity should incorporate not only weight stigma but also racism and multiple forms of discrimination.